2009
DOI: 10.1016/j.jenvman.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of cultural models in local perceptions of SFM – Differences and similarities of interest groups from three boreal regions

Abstract: Differences in the way local and regional interest groups perceive Sustainable Forest Management in regions with different forest use histories were studied using Southeastern Finland, the Mauricie in Quebec and Central Labrador in Canada as examples of regions with high, medium and low importance of commercial forestry. We present a conceptual model illustrating the cyclic interaction between the forest, cultural models about forests and forest management. We hypothesized that peoples' perceptions would be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…These factors have created a sense of local ownership over natural resources hence create the development of positive attitudes by residents towards tourism and conservation. Berninger et al (2009) argue that local natural and socio-cultural conditions, public discourse and individual experiences contribute to local attitudes towards conservation. This, therefore shows that it's not only economic benefits that determine resident attitudes towards conservation.…”
Section: Rankingsmentioning
confidence: 99%
“…These factors have created a sense of local ownership over natural resources hence create the development of positive attitudes by residents towards tourism and conservation. Berninger et al (2009) argue that local natural and socio-cultural conditions, public discourse and individual experiences contribute to local attitudes towards conservation. This, therefore shows that it's not only economic benefits that determine resident attitudes towards conservation.…”
Section: Rankingsmentioning
confidence: 99%
“…The number of indicators used was limited since we wanted to reduce the cognitive load to the participants. The goal was to select indicators that reflect the important factors and preferred indicators suggested by the local people as described in Berninger et al (2009). The amount of roads is both used as an economic indicator of logging costs and an ecological indicator of habitat fragmentation.…”
Section: Study Area Modeling and Simulationsmentioning
confidence: 99%
“…The only empirical international comparison concerning professionals' values has been Berninger et al (2008) who found that these values varied between countries depending on the relative role of forestry. Their data came from three regions in Finland and Canada and showed in particular that as the importance of commercial forestry increased, the more the importance of economic issues was expressed.…”
Section: Introductionmentioning
confidence: 99%